IMPLEMENTATION OF THE PARALON OBSTACLES TO INCREASE LEARNING OUTCOMES OF THE SQUAT STYLE LONG JUMP IN CLASS VII STUDENTS OF SMP N 16 SURAKARTA - Shodiq Hutomono; Teguh Santosa; Joko Sulistiyono, (Journal Of Indonesia Sport Education and Adapted Physical Education (JISEAPE), 2022)
The aim of this research is to determine the improvement in learning outcomes for squatting long jump using paralon obstacle aids in class VII students at SMP N 16 Surakarta. The method used in this research is classroom action research. The subjects of this research were class VII students at SMP N 16 Surakarta with a total of 34 students. Data was collected using long jump practice tests and questionnaires. Data were analyzed using paired t-test.The results of the research showed that there was a significant increase in learning achievement after the application of paralon obstacle aids to students at SMP N 16 Surakarta in learning the squat style long jump. This is proven by the t test value of 11.958 for paralon with a height of 40 cm. and the t test value is 12.238 for paralon with a height of 50 cm. The jump results without paralon aids had an average of 1.88 m, with 40 cm paralon aids the results were an average of 2.08 m, and with 50 cm paralon aids the results averaged 2.29 m.